Protótipo de sistema tutor inteligente para avaliação de aluno em ambiente virtual de aprendizagem com intercâmbio de dados em JSON - Perin, Ana Paula Juliana (2017)
In the contemporary world, the presence of digital technologies such as computers, tablets and smartphones added to social networks makes the creation and exchange of information grow exponentially. With so much information available, the possibilities for developing knowledge generation activities increase, not only in the school context, but in any context. School education can use this large availability of information and connectivity to develop new ways of teaching to improve the learning of its students. Virtual learning environments enter into this context as a mediator between disciplines and students, enabling teachers to send activities, archives, content and other resources aimed at education. Generally, such environments do not have an adaptability of activities or contents according to student learning. Intelligent Tutors provide the tools to decrease textit GAP between what exists and what it would be ideal to have. The objective of this work is to develop an Intelligent Activity-Based Tutorial Prototype based on virtual learning environments using data exchange using JSON technology, which allows any programming language to receive and send data quickly and independently of platform. The results have been satisfactory because it concludes with a functional tool with possibilities of continuation and expansion, since the code is free for use, improvements and distribution. This work is expected to contribute to society, especially in computer mediated education.